The Characterization of Dry Fermented Sausages under the “Chorizo Zamorano” Quality Label: The Application of an Alternative Statistical Approach - Javier Plaza; Carmelo Ávila-Zarza; Ana María Vivar-Quintana; Isabel Revilla (Foods, 2023)
The characterization of quality brand meat products, such as “Chorizo Zamorano” dry fermented sausages, involves a wide range of data which makes it necessary to use alternative statistical methodologies. In this study, the feasibility of the Categorical Principal Components Analysis as a multivariate non-linear technique for the characterization of “Chorizo Zamorano” was assessed. The data analyzed were those of eight commercial brands covered by the quality mark over an eight-year period (2013–2020) and included parameters of the physicochemical composition and organoleptic properties of the product. The results showed that “Chorizo Zamorano” has an average moisture content (28.28%), high protein (38.38%) and fat (51.05%) contents, and a very low carbohydrate concentration (1.52%). Results showed that the fat and protein content and the sensory parameters related to external and internal odor appeared to be the studied variables with the greatest influence on the classification of the products according to their quality.